A study on the determination of handgrip strength of Olympic style weightlifting athletes - Erdagi, K.; Tüfekçi, O.; Yeseri, M.; Yüksel, M. F.; Turgut, N.; Eroglu, B. E. (Physical Education of Students, 2020)
Handgrip strength is widely accepted as a functionality parameter to assess upper extremity performance. The measurement of hand grip strength by dynamometry is a low cost, non-invasive method of simple applicability. The present study is based on the association of dominant and non-dominant handgrip strength with demographic and anthropometric characteristics; height, body weight, body mass index, upper arm length, forearm length, hand length, forearm circumference, upper arm circumference.Material: The study included 70 male athletes in olympic style weightlifting (age: 18.06±2.18, height:1.74±.06 m, body weight: 76.09±13.04 kg). A total of 70 sedentary individuals as a control group (age 18.11±.18, height:1.75±.04 m, body weight: 74.01±13.94 kg) were also taken to compare study findings. The data obtained was analyzed by SPPS for Windows, version 25. Handgrip strength measurements were obtained by a Jamar dynamometer, according to the recommendations of the American Association of Hand Therapists. Results: It was found that the values of dominant and non-dominant handgrip strength, upper arm circumference and forearm circumference length of the weightlifting athletes were higher than those of sedentary individuals (p<.001). No asymmetry was observed in dominant and non-dominant handgrip strength values of the athletes and sedentary individuals. The correlations were noted between dominant and non-dominant handgrip strength values of weightlifting athletes and demographic characteristics, some anthropometric characteristics of upper extremity and weightlifting performance. Conclusions: The variability of handgrip strength might largely be explained by some anthropometric characteristics of upper extremity